The complete mitochondrial genome of long-tailed red-toothed shrew (Episoriculus leucops) and implication of phylogenetic status. Issue 4 (3rd April 2021) - Chen, Dan; Qin, Boxin; Xie, Fei; Wang, Qiong; Chen, Shunde
Abstract: We determined a complete mitochondrial genome of Episoriculus leucops . This mitogenome is a circular molecule with 16, 838 bp in length, containing 13 protein-coding genes, 22 transfer RNA genes (tRNA), and two ribosomal RNA genes (rRNA). This mitochondrial genome has a base composition of 32.8% A, 29.2% T, 24.9% C, and 13.1% G. We reconstructed Bayesian phylogenetic tree by taking advantage of 19 species belonging to subfamily Soricinae. Phylogenetic tree shows that the long-tailed red-toothed shrew belongs to genus Episoriculus, and it is the closest relationship with E. caudatus. This mitochondrial genome provides an important resource for addressing taxonomic issues and studying molecular evolution.